Ten picrotoxane-type sesquiterpenoids from the stems of Dendrobium wardianum Warner. (October 2021) - Fan, Wei-Wei; Yang, Dan; Cheng, Zhong-Quan; Xu, Feng-Qing; Dong, Fa-Wu; Wei, Xiao-Yong; Hu, Jiang-Miao
Abstract: Ten undescribed picrotoxane-type sesquiterpenoids, dendrowardins A–J, together with two known ones, were isolated from the stems of Dendrobium wardianum Warner (Orchidaceae). Dendrowardins A–D feature the unusual 5, 2- δ -lactone and additionally dendrowardins C–D are the first examples containing the 11, 10- γ -lactone moiety. The structures were established using spectroscopic methods and by comparison with literature data. Further, dendrowardin E, amotin, and aduncin exhibited significant effects of promoting the proliferation on human lens epithelial cells (HLECs) induced by D-galactose. Graphical abstract: Image 1 Highlights: Ten undescribed picrotoxane-type sesquiterpenoids dendrowardins A–J . Picrotoxane sesquiterpenoids contain 5, 2- δ -lactone and 11, 10-γ-lactone moiety.